2021
DOI: 10.1016/j.breast.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Addressing disparities and challenges in underserved patient populations with metastatic breast cancer in Europe

Abstract: People with metastatic breast cancer face many challenges and disparities in obtaining optimal cancer care. These challenges are accentuated in underserved patient populations across Europe, who are less likely to receive quality healthcare for reasons including socioeconomic inequalities, educational or cultural status, or geographic location. While there are many local and national initiatives targeted to address these challenges, there remains a need to reduce disparities and improve access to healthcare to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Participation in clinical trials itself may ameliorate observed disparities in cancer outcomes, because clinical trials can provide access to evidence‐based medicines 58,59 . Achieving cancer health equity through optimizing diversity in clinical trials is a national and global imperative, and everyone has a role to play 24,36,60 …”
Section: What Can We Do About It?mentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in clinical trials itself may ameliorate observed disparities in cancer outcomes, because clinical trials can provide access to evidence‐based medicines 58,59 . Achieving cancer health equity through optimizing diversity in clinical trials is a national and global imperative, and everyone has a role to play 24,36,60 …”
Section: What Can We Do About It?mentioning
confidence: 99%
“…58,59 Achieving cancer health equity through optimizing diversity in clinical trials is a national and global imperative, and everyone has a role to play. 24,36,60…”
Section: Uniform Reporting Of Study Outcomesmentioning
confidence: 99%
“…Among patients with advanced breast cancer there are a number of challenges that contribute to disparities in outcomes among underserved patient populations. Such disparities have been classified at the level of the individual or at a healthcare system level in a recent pan-European study that convened an expert panel ( 12 ). A number of challenges faced by underserved patient populations were identified including awareness, issues with communication, cultural factors, issues with data collection and clinical trial participation, issues with implementation of high-quality guidelines, and some workplace issues ( 12 ).…”
Section: World-wide Socioeconomic Status Health Care Expenditures Amentioning
confidence: 99%
“…Such disparities have been classified at the level of the individual or at a healthcare system level in a recent pan-European study that convened an expert panel ( 12 ). A number of challenges faced by underserved patient populations were identified including awareness, issues with communication, cultural factors, issues with data collection and clinical trial participation, issues with implementation of high-quality guidelines, and some workplace issues ( 12 ). Coordinated efforts, including cooperation between countries, to address the challenges that lead to healthcare disparities among patients with metastatic breast cancer could improve outcomes and reduce disparities among the underserved patient populations ( 12 ).…”
Section: World-wide Socioeconomic Status Health Care Expenditures Amentioning
confidence: 99%
“…Survivor- and oncologist-led cancer CSOs were established to fill gaps in public health care systems and worked to lift stigma of cancer as a death sentence, improve early detection, and increase access to cancer treatment and psychosocial support. 17 19 A deeper understanding of experiences and priorities of breast cancer CSOs in the region has the potential to help patient advocates and oncologists to improve cancer care. 20 24 …”
Section: Introductionmentioning
confidence: 99%